Correction of temporal misregistration artifacts in jet flow by conventional phase-contrast MRI - Doyle, Mark W.; Kortright, Eduardo; Anayiotos, Andreas (My University, 2007)
Purpose: To show that accuracy of jet flow representation by magnetic resonance (MR) phase-contrast (PC) velocity-encoded (VE) cine imaging is dominated by error terms resulting from the temporal distribution of data, and to present a generally applicable data interpolation-based approach to correct for this phenomenon. Materials and Methods: Phase-contrast data were acquired in a stenotic orifice flow phantom using a physiologic pulsatile flow waveform. A temporally registered scan, acquired without data segmentation or interleaving was obtained (17 minutes) and taken as the reference (REF). Conventional PC data sets were acquired using segmentation and data interleaving. An enhanced temporal registration (ETR) algorithm was applied to the acquired data to temporally interpolate component sets and output data at matching time points, thereby reducing temporal dispersion. Results: Compared to the REF data, conventionally processed PC data consistently overestimated peak velocities in laminar jet flow regions (127% ± 28%) and exhibited relatively weak correlations (r = 0.67 ± 0.23). The ETR-processed data better represented peak velocities (101% ± 13%, P < 0.001) and correlated more closely with the REF data (r = 0.94 ± 0.05. P < 0.001). Conclusion: The temporal distribution of PC data impacts the accuracy of velocity representation in pulsatile jet flow. A temporal registration postprocessing algorithm can minimize loss of accuracy.
Keywords: Data processing; Jets--Fluid dynamics; k-spaces; Magnetic resonance imaging